Dynamics of cytokine profile indexes in children with first diagnosed pulmonary tuberculosis in the course of antimycobacterial therapy - Raznatovska, O. M.; Mironchuk, Yu. V. (Zaporozhye Medical Journal, 2018)
Antimycobacterial therapy is the main method of tuberculosis treatment. But some antimycobacterial medications have an unfavorable influence on the immune system and this fact significantly decreases efficiency of treatment and requires an additional pathogenetic immunocorrection. The aim of the work – to research dynamics of cytokine profile indexes in blood serum of children with first diagnosed pulmonary tuberculosis in the course of antimycobacterial therapy depending on specific process prevalence and to assess efficiency of antimycobacterial therapy after the basic course of treatment completion for further immunocorrecting therapy development. Materials and methods. Study of cytokine profile indexes was performed in 28 children with first diagnosed pulmonary tuberculosis from 1 to 16 years old (the average age was 9.2 ± 1.1 years). Depending on the specific process prevalence children with first diagnosed pulmonary tuberculosis were divided into two groups: the first group included 17 persons with a disseminated process and the second group included 11 persons with an isolated process. The comparison group included 30 healthy children. Comparison groups were age-matched and gender-matched. Cytokine profile indexes were studied by means of IL-2, IL-6, IL-4, IL-10 levels detection in blood serum through enzyme-linked immunosorbent assay using immunoenzymometric reader Sirio S and a set “Bender MedSystems GmbH” (Austria), (pg/ml). Dynamics of cytokine indexes was studied at the beginning of the antimycobacterial therapy intensive phase, on completion of the antimycobacterial therapy intensive phase (2 months after treatment) and on completion of the antimycobacterial therapy maintenance phase (6 months after treatment). Parents of all sick children signed patient’s written informed consent for participation in this study. Results of this work were processed by the modern methods of analysis with the help of a personal computer and the statistical package of the licensed software program Statistica® for Windows 6.0 (StatSoft Inc., № AXXR712 D833214FAN5). Results. A significantly high level of pro-inflammatory cytokine IL-2 characterized Тh1-type of cellular immune response high activity in children with first diagnosed pulmonary disseminated tuberculosisthroughout the entire course of antimycobacterial therapy. And significantly stably low levels of anti-inflammatory cytokines IL-4 and IL-10 indicated insufficiency of anti-inflammatory response throughout the entire course of antimycobacterial therapy. Calculation of cytokine indexes (and namely the IL-2/IL-10 ratio) has conformed that there was a disbalance between pro-inflammatory and anti-inflammatory cytokines towards pro-inflammatory cytokines with predominance of Тh1-type cellular immune response which lasted during the entire course of antimycobacterial therapy and tended to decline on its completion. Even though that in the course of antimycobacterial therapy in children with bacterioexcretion this process stopped, average duration of in-patient treatment was 9–10 months and that was 3 months longer than standard treatment of patients with first diagnosed pulmonary tuberculosis. The warning sign is also that among children with disseminated tuberculosis there were 3 cases (17.6 %) of multidrug-resistant tuberculosis in the course of treatment and in case with 1 child (5.9 %) lung destruction was persisted on the treatment completion. Conclusions. Children with first diagnosed pulmonary tuberculosis (regardless of the specific process prevalence) had a high activity of Th1-type cellular immune response against the background of an extremely decreased activity of Th2-type cellular immune response throughout the entire course of antimycobacterial therapy. This fact indicates insufficiency of anti-inflammatory response. At the same time all children had a pronounced disbalance between pro-inflammatory and anti-inflammatory cytokines towards pro-inflammatory ones on completion of the treatment basic course. These changes may contribute to the specific process progression as well as early recurrences of the disease.